URGENSI ASESMEN DALAM PENYUSUNAN PROGRAM BIMBINGAN DAN KONSELING DI SEKOLAH MENENGAH - Mustika, Erika Winda; Zahro, Putri Awalia; Habsy, Bakhrudin All (Consilium: Education and Counseling Journal, 2024)
Guidance and counseling are aspects that cannot be separated from education. Education is not just a teaching and learning process, but will also influence the problems experienced by students. In its implementation, guidance and counseling teachers are professional figures who will help serve students in achieving development. Students need guidance and counseling because they still lack knowledge regarding themselves and their environment. Guidance and counseling teachers need valid data to describe students' needs. For this reason, it is hoped that the existence of assessments can be a tool in knowing the needs of each student. Where the results of the assessment will help guidance and counseling teachers in implementing guidance and counseling programs. A guidance and counseling program will not run efficiently if its implementation is not systematic and not aligned with a quality management system. In this research, the author used a qualitative method in the nature of a literature study. This method requires books or other literature as the main material. So it is found that assessment has an important role in implementing guidance and counseling programs. The assessment will later be able to help guidance and counseling teachers in making accurate diagnoses, developing effective action plans, increasing students' self-related knowledge, and so on. The stages in preparing a guidance and counseling program so that it runs effectively are as follows: a). preparation stage, which includes assessment b). Design stages, which include preparing annual and semester guidance and counseling programs. Keywords: Assessment, guidance and counseling program, urgency of assessment